Coordinated Portfolio Investment Survey Guide (Third Edition) - Josyula, Venkat (Manuals and Guides, 2018)
This third edition of the Coordinated Portfolio Investment Survey Guide has been prepared to assist economies that participate or are preparing to participate in the Coordinated Portfolio Investment Survey (CPIS). It builds on and updates the second edition of the CPIS Guide (2002) to reflect the adoption of the Balance of Payments and International Investment Position Manual, sixth edition (BPM6) as the standard framework for compiling cross-border position statistics.